Relationships between the Psychoemotional State of Middle-Aged People and their Physical Activity Levels - Pranas Mockus; Asta Mockienė; Diana Karanauskienė; Vida Janina Česnaitienė (Lithuanian Sports University, 2020)
Background. Constantly accelerating pace of life, heavy workloads, and new technologies coming into our lives lead to mental health problems - stress, anxiety, and depression, which causes uncontrollable physical health problems. The relationship between individual PA domains and physical activity intensity in middle-aged individuals as well as their psycho-emotional status have not been sufficiently explored. The aim of the study was to determine the relationship between psycho-emotional state and physical activity levels in middle-aged people. Methods. The epidemiological method was chosen for the study. The chosen method of data collection was an anonymous questionnaire survey. Results. Assessing the psycho-emotional state of the subjects, we found that 17.8% of women and men studied were experiencing stress. More women (45%) than men (27.5%) experienced nervous tension, and more men (25.5%) than women (13.7%) experienced stress. High levels of physical activity were found in more than 2/3 of the subjects (73.5%). The distributions of women and men did not differ much according to the level of physical activity (74.3, 72.0%). Conclusion. A higher level of physical activity was associated with a better assessment of nervous tension and stress - more physically active individuals experience less nervous tension and stress. People who spent more time sitting on weekdays and at weekends experienced more nervous tension and stress. Keywords: physical activity levels, psychoemotional state, sedentary lifestyle, physically active lifestyle, nervous tension and stress.